2022
DOI: 10.3389/fendo.2022.965545
|View full text |Cite
|
Sign up to set email alerts
|

Association of estimated glomerular filtration rate and incident pre-diabetes: A secondary 5-year longitudinal cohort study in Chinese people

Abstract: ObjectiveThere is still limited evidence regarding the relationship between the estimated glomerular filtration rate (eGFR) and pre-diabetes. For that reason, our research aims to survey the association of eGFR with pre-diabetes.MethodsThis study was a retrospective cohort study, which consecutively and non-selectively collected a total of 173301 participants from Rich Healthcare Group in China from January 2010 to 2016. We then used the Cox proportional-hazards regression model to explore the relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Likewise, a population-based cohort study conducted in Taiwan identified CKD as a crucial and independent predictor of diabetes, with an adjusted HR of 1.204 and a 95% CI of 1.11 to 1.31[ 52 ]. Our previous research also discovered that decreased eGFR was strongly linked to a higher risk of developing both diabetes (HR = 0.986, 95% CI 0.984, 0.988) [ 20 ] and pre-diabetes (HR = 0.993, 95% CI 0.992–0.995) [ 21 ] in the general Chinese population. Given this information, we posited that a diminished eGFR might be linked to a decreased likelihood of returning to normoglycemic levels from a state of IFG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, a population-based cohort study conducted in Taiwan identified CKD as a crucial and independent predictor of diabetes, with an adjusted HR of 1.204 and a 95% CI of 1.11 to 1.31[ 52 ]. Our previous research also discovered that decreased eGFR was strongly linked to a higher risk of developing both diabetes (HR = 0.986, 95% CI 0.984, 0.988) [ 20 ] and pre-diabetes (HR = 0.993, 95% CI 0.992–0.995) [ 21 ] in the general Chinese population. Given this information, we posited that a diminished eGFR might be linked to a decreased likelihood of returning to normoglycemic levels from a state of IFG.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a Chinese study found that, in healthy individuals, FPG (but not 2-h post-load blood glucose or glycated hemoglobin A1c) was linked to a mild decline in eGFR [ 19 ]. Prior community-based investigations in China have demonstrated an inverse and non-linear correlation between eGFR and the hazards of diabetes and pre-diabetes [ 20 , 21 ]. Nevertheless, extant literature does not provide any indication of a relationship between eGFR (both lower and higher levels) and pre-diabetes regression to normoglycemia.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking status was categorized into three distinct groups according to individuals’ smoking behavior: current smokers, individuals who have smoked in the past, and individuals who have never smoked. Similarly, drinking status was classified into three categories based on individuals’ drinking behavior: current drinkers, individuals who have previously consumed alcohol, and individuals who have never consumed alcohol ( 28 ). Daily activity was defined as engaging in at least 1.25 hours of vigorous activity per week, 2.5 hours of moderate-intensity activity per week, or a combination of both (equivalent to at least 600 metabolic equivalent minutes per week) ( 29 ).…”
Section: Methodsmentioning
confidence: 99%
“…Covariates were selected based on previous research and our clinical knowledge (17,23,27). The following factors were included as covariates: (i) categorical variables: diabetes mellitus (DM), sex, hypertension, chronic lung disease (CLD), smoking status, coronary heart disease (CHD), drinking status, chronic kidney disease(CKD), daily activity, antihypertensive drug use, antihyperglycemic drug use, antihyperlipidemic drug use, malignant tumors, mental disease,; (ii) continuous variables: age, white blood cell (WBC), hs-CRP, HGB, blood urea nitrogen (BUN), PLT, body mass index (BMI), diastolic blood pressure (DBP), TG, systolic blood pressure (SBP), UA, hemoglobin A1c (HbA1c), and serum creatinine (Scr).…”
Section: Covariatesmentioning
confidence: 99%